HAK PEREMPUAN UNTUK PENDIDIKAN DAN PENGAJARAN DALAM PERSPEKTIF ISLAM - Sadari Sadari (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Women and men are always ditimpangkan on the right to education. The form of inequality is, a man free to choose in reaching any high education. While the woman was very difficult and even squeezed to achieve their right to education even in the process of belajarpun must be separated. Difficulty in obtaining educational opportunities, because there are many factors among which are the factors of history, culture and religion (doctrine). Whatever the factors women must find new momentum that, a wanitapun have equal contribution in building the nation, so we need to get right both in education and teaching. In Islamic teaching both men and women have egalitarian relationships and man's most noble before God are those who fear both men and women. Therefore, this article explains the importance of gender mainstreaming (gender mainstreaming) in education and teaching.